Training recommendations based on match characteristics of professional singles tennis - Morante, S. (Medicine and Science in Tennis, 2006)
The science of training in professional tennis has significantly increased over the past decades in response to various factors, including increased depth in standard, commercial and competitive pressures, and heavier tournament schedules. In order to be competitive at this level, players must spend many hours of physical conditioning "off court" to complement their hitting and match practice. These areas are not only important to maximizing competitive performance but also assist to reduce injuries that may result from the higher stresses of play and the demanding professional tour schedule. Necessary modifications in technique are often difficult to make since the competitive phase lasts almost an entire year, with any missed tournaments resulting in failure to achieve valuable points for rankings. Thus, the principle of specificity should be employed in every training program, to ensure maximum effectiveness and efficiency. The principle of specificity states that training is of the greatest benefit when it reflects the requirements of the actual performance. Consequently, optimal competitive tennis performance would be achieved through a training program that is similar to the characteristics and demands of match play. A number of previous studies have investigated the match characteristics of professional singles tennis. This paper discusses training applications based on these findings in relation to the principle of specificity.